2022
DOI: 10.1037/law0000325
|View full text |Cite
|
Sign up to set email alerts
|

Diversion as a pathway to improving service utilization among at-risk youth.

Abstract: Despite the high rates of mental illness among youth in the juvenile justice system, many justiceinvolved youth do not receive adequate behavioral health services. We examined differences in health service utilization outcomes between youth who were diverted through a community-based, precomplaint program (Safety Net; n = 41), and youth with juvenile justice involvement in neighboring cities (n = 154). Individual arrest and health care records were combined to evaluate the rate of health care service utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…Resource officers were trained in juvenile mental health needs, and youth who committed an arrestable offense could be diverted from formal system involvement by the resources officer and instead be connected to needed services. Findings showed that youth participating in the program experienced increased outpatient service utilization compared with the reference group (Barrett et al, 2022); recidivism was not measured in this study.…”
Section: Mental Health Diversion Programscontrasting
confidence: 57%
“…Resource officers were trained in juvenile mental health needs, and youth who committed an arrestable offense could be diverted from formal system involvement by the resources officer and instead be connected to needed services. Findings showed that youth participating in the program experienced increased outpatient service utilization compared with the reference group (Barrett et al, 2022); recidivism was not measured in this study.…”
Section: Mental Health Diversion Programscontrasting
confidence: 57%
“…Indeed, many school policing programs have been associated with increases in juvenile arrests and dropouts which furthers the school-to-prison pipeline (Hemez et al, 2020). In contrast, the Safety Net Collaborative has been able to demonstrate success in reducing juvenile arrests (Barrett & Janopaul-Naylor, 2016), reducing recidivism (Barrett et al, 2019) and connecting diverted youth to behavioral health services (Barrett et al, 2021;Janopaul-Naylor et al, 2019). While the quan-titative data has demonstrated support for cities and towns adopting diversion models similar to Safety Net, what has been missing from the evidence base are the stories of lived experience from police officers involved in Safety Net, community partners and participating families.…”
Section: Discussionmentioning
confidence: 99%
“…The Safety Net Collaborative is comprised of nine specially trained Youth Resource Officers (YROs), a psychologist, a social worker and community partners from the schools, afterschool programs and community social services providers. The goal of the program, Safety Net Collaborative, is to reduce involvement in the juvenile justice system, increase graduation rates, improve relations between the community, at‐risk youth, their families, and law enforcement, and increase collaboration between the police department and community partners (Barrett et al, 2021; Barrett & Janopaul‐Naylor, 2016). To accomplish this goal, Safety Net works at the juncture of the criminal justice and behavioral healthcare systems, identifying behavioral health problems and building connections to appropriate services, especially when arrestable offenses may be triggered by underlying behavioral health issues.…”
Section: Safety Net Collaborativementioning
confidence: 99%
See 1 more Smart Citation
“…Community-based diversion and treatment-oriented programs that redirect youth offenders from the legal system are found to be more effective at preventing recidivism compared with the conventional prosecution process. 53 , 54 , 55 Diversion programs based on restorative justice models are shown to be particularly promising. A meta-analysis found that youths participating in restorative diversion programs were more than 75% less likely to be rearrested in the year or 2 following diversion than court-processed youths.…”
Section: Discussionmentioning
confidence: 99%